2003
DOI: 10.1590/s0102-311x2003000500007
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição espacial da leptospirose no Rio Grande do Sul, Brasil: recuperando a ecologia dos estudos ecológicos

Abstract: Leptospirosis is an endemic disease in the State of Rio Grande do Sul, Brazil, and presents a broad diversity of exposure routes, reservoirs, etiological agents, and clinical features. The main objective of this work is to identify transmission areas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
15

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 24 publications
2
28
0
15
Order By: Relevance
“…Num estudo da distribuição espacial da leptospirose no Rio Grande do Sul, Barcellos et al (2003) identiϐicaram áreas de maior risco e possíveis componentes ecológicos da transmissão da leptospirose. As maiores taxas de ocorrência da doença foram veriϐicadas em áreas litorâneas, de baixa altitude e uso do solo predominantemente agrícola, de lavoura irrigada.…”
Section: Discussionunclassified
“…Num estudo da distribuição espacial da leptospirose no Rio Grande do Sul, Barcellos et al (2003) identiϐicaram áreas de maior risco e possíveis componentes ecológicos da transmissão da leptospirose. As maiores taxas de ocorrência da doença foram veriϐicadas em áreas litorâneas, de baixa altitude e uso do solo predominantemente agrícola, de lavoura irrigada.…”
Section: Discussionunclassified
“…By choosing spatial units for data clustering that best highlight the social and environmental processes, processes that occur at scales differing from political-administrative divisions can be better understood. 2 Most ecological studies within epidemiology use political-administrative divisions as the unit for analysis and investigation of disease transmission patterns a posteriori. On the other hand, in the present study, it was sought to identify areas of greater transmission of dengue based on clustering in areas constructed a priori, through environmental, socioeconomic and demographic criteria.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, these areas do not always represent the reality involved in the epidemiological dynamics of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…In the city of Belo Horizonte, state of Minas Gerais, southeastern region, Figueiredo et al 10 observed that cases were registered predominantly in regions without adequate sanitary infrastructure, urban development conditions and garbage collection. In a study in the state of Rio Grande do Sul, southern region, Barcellos et al 4 noted that the highest incidence rates were in humid coastal areas at low altitude (subject to fl ooding) with land used for agricultural purposes. In the city of Rio de Janeiro, southeastern region, Tassinari et al 18 reported on the occurrence of an epidemic following heavy storms.…”
mentioning
confidence: 99%